The personal is political. Moral authoritarianism and female teachers in the Uruguayan dictatorship (1973-1984) - Sempol, Diego (Elephant & Castle, 2023)
This article analyzes the forms of moral persecution deployed against primary education teachers during the Uruguayan dictatorial regime (1973-1984), seeking to address the modalities shown in the evolution of a long-term State paternalism and the curbs imposed on emerging generational changes in gender relations through the institutional promotion of a binary and traditional model.